2004
DOI: 10.1038/modpathol.3800030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pathological risk factors for lymph node metastasis of submucosal invasive colon cancer

Abstract: There are currently no universally accepted indications and criteria for additional surgical resection of the colorectum after endoscopic resection of the submucosal invasive cancer. The purpose of the present study is to establish accurate indications and criteria for additional surgical resection of the colorectum, based on the prediction of lymph node metastasis, after endoscopic resection of the submucosal invasive cancer. We investigated 140 submucosal invasive colorectal cancers and analyzed the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
1
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 13 publications
5
89
1
7
Order By: Relevance
“…Many investigators have reported that submucosal invasion depth is a risk factor for lymph node metastasis. [1][2][3][4][5][6][7] However, problems exist with measurement of the depth of submucosal invasion when the muscularis mucosa is completely disrupted by tumor invasion. In such cases, measured submucosal invasion depths might be inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many investigators have reported that submucosal invasion depth is a risk factor for lymph node metastasis. [1][2][3][4][5][6][7] However, problems exist with measurement of the depth of submucosal invasion when the muscularis mucosa is completely disrupted by tumor invasion. In such cases, measured submucosal invasion depths might be inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous reports have analyzed only small numbers of dissected lymph nodes: 7.3±4.9 lymph nodes in the study by Nascimbeni et al, 3 and a median number of 10 in the study by Okabe et al, 5 whereas the number of removed lymph nodes was not described in several other reports. 4,6,7 Wang et al 12 showed that the total number of sampled lymph nodes was associated with the prognosis of submucosal invasive colorectal carcinoma. Therefore, accurate diagnosis of lymph node status by retrieving a sufficient number of nodes is essential for examining the relationship between clinicopathological factors and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one of the studies, all the cases were all initially treated by surgical resection (Egashira et al, 2004). Masaki et al (Masaki et al, 2001b) showed that expression of MMP-7 (a matrix metalloproteinase) at the invasive margin of T1 cancers was significantly associated with other poor histological features and unfavourable outcome.…”
Section: Cribriform Histologymentioning
confidence: 99%